Specifics of the prosecutor’s participation in arbitration proceedings as a third party without independent requirements - I.I. Golovko (Известия высших учебных заведений. Поволжский регион: Общественные науки, 2021)
Background. The normative legal basis for the participation of the prosecutor in arbitration proceedings does not fully and accurately determine the features of the prosecutor’s activities. The noted problem is also typical for the participation of the prosecutor in the case as a third party. In this regard, attention is drawn to the practice of the participation of the prosecutor in the consideration of cases by the courts. Materials and methods. The solution of research problems is ensured by an appeal to the legislation, the selection and study of materials from judicial practice. This made it possible to identify the peculiarities of the participation of the prosecutor in arbitration proceedings as a third party. Results. The features of the legal regulation of the participation of the prosecutor in the procedural situation of a third party have been investigated. Typical situations of the participation of the prosecutor in the case are generalized, the tasks that the prosecutor solves in this case are established. The features of the powers of the prosecutor participating in the case in the role of a third party and in the case of intervening in the case to give an opinion are compared. Conclusions. The grounds for the participation of the prosecutor in arbitration proceedings as a third party have been determined. The violations committed by the courts in the determination of the procedural position of the prosecutor were revealed. The conclusion is made about the need to improve the legislation on the participation of the prosecutor in arbitration proceedings.